Fluid mechanics analysis in volleyball services - Depra, P.; Brenzikofer, R.; Goes, M.; Barros, R. (coachesinfo.com, 1998)
The service is considered the first attack action in volleyball games. Most types of services can be recognized through the athlete's posture before he hits the ball. Frequently this information is not enough to prepare an adequate reception. Erratic behavior seems to appear along the trajectory hindering the reception. This work focuses on the characterization of the service ball's trajectories. This work allowed us to quantify kinetic and dynamic variables of the trajectories of twenty-six volleyball service balls thrown by an high level athlete. We observed that all services are placed in the region of the called "drag crisis" and present a great variation of the drag coefficient. We observed that the four analyzed services show orderly clusters in a growing sequence of Reynolds Numbers: underhand service, floater, floater with jumping and overhand service with jumping. The drag force is up to 1.4 times superior to the weight force of the ball. All these kind of quantification may also be used to compare the characteristics of different players.